Religion and science : historical and contemporary issues - Barbour, Ian G.; Barbour, Ian G. ([San Francisco] : HarperSanFrancisco, 1997)
Contains essays in which the author explores interactions between science and religion in the seventeenth, eighteenth, and nineteenth centuries, and examines contemporary methods and theories of science and their implications for concepts of God and human nature.
"Revised and expanded edition of Religion in an age of science.".
Includes bibliographical references and indexes.
Adult
Keywords: Religion and science; Religion and science